Design and test of bionic wide-ridge soybean tilling-sowing machine - Jia, Honglei; Guo, Mingzhuo; Zhao, Jiale; Huang, Dongyan; Zhuang, Jian; Qi, Jiangtao (International Journal of Agricultural and Biological Engineering, 2019)
The insufficient accumulated temperature of the plow layer during spring tillage in Northeast China severely restricts soybean root growth and whole-plant development. High regional soil viscosity further complicates tilling-sowing. In order to seek a solution to these problems, field comparative tests were conducted to investigate the effects of shallow-loosening (SL) and reshaping ridge (RR) on soil temperature and soybean root growth. Compared with conventional tillage (CT), SL and RR significantly increased the soil temperatures within 0-25 cm (p < 0.05) and 0-15 cm (p < 0.05), respectively. In particular, higher soil temperature within 15-25 cm was established after SL than after RR (p < 0.05). Additionally, SL promoted substantially more vigorous soybean development (seedling height) than RR (p < 0.05), which in turn led to a significant outperformance over CT (p < 0.05). Further, bionics, reverse engineering, and curve fitting were combined to design a hare claw toe bionic shallow-loosening shovel and a pangolin scale bionic ridging shovel with anti-drag functions. Field verification tests confirmed that these two bionic tillage devices outperformed the conventional tillage device in reducing tractive drag by 13%-19%. Based on the results of these tests, a 2BGD-6(110) bionic wide-ridge soybean tilling-sowing machine was designed, which was capable of shallow-loosening, reshaping ridge and sowing. The new machine significantly reduced the tractive drag, efficiently loosened the soil, increased soil temperature, and accelerated soybean root growth. This study can provide a theoretical and practical reference for soybean production in Northeast China. Keywords: bionics, tillage, shallow-loosening, soybean, reshaping ridge, soil temperature DOI: 10.25165/j.ijabe.20191201.4014 Citation: Jia H L, Guo M Z, Zhao J L, Huang D Y, Zhuang J, Qi J T. Design and test of bionic wide-ridge soybean tilling-sowing machine. Int J Agric & Biol Eng, 2019; 12(1): 42–51.